Transaxillary Patent Ductus Arteriosus Ligation without Chest Drainage - Hasan, Kazi Abul; Islam, Md Zahidul; Siraji, Md Saiful Islam; Rushel, Khondokar Shamim Shahriar Ziban; Ferdous, Shahanaz (Journal of Armed Forces Medical College, Bangladesh, 2020)
Introduction: Chest drain insertions after patent ductus arteriosus (PDA) ligation creates significant morbidity interms of pain, infection, reduce mobility as well as prolonged hospital stay. Objectives: To evaluates postoperative outcomes of chest closure with or without insertion of drain following PDA ligation through transaxillary route. Materials and Methods: Data was collected retrospectively from 48 pediatric patients underwent PDA ligation at National Institute of Cardiovascular Disease and Ibn Sina hospital over a period of 3 years (January 2015- May 2018). Participants were divided into two groups of chest closure without or with chest tube insertion. All continuous data presented as mean± standard deviation. Result: PDA ligation was performed 48 patients through left trans axillary thoracotomy of whom 20 patients chest closure were done without drain tube and 28 patients with drain tube. Age range was 6 months to 7 years. The mean duration of surgery was 65±18 minutes in no drain tube group and 68±21 minutes with drain tube group. There were minimal blood loss and no blood transfusion require in both groups. No fluid accumulation in both groups. One patient in no drain group developed small pneumothorax and one developed surgical emphysema in drain group. Postoperative analgesia and oxygen requirement were less in no drain group than drain group. Postoperative hospital stay was 2.25±0.53 days in no drain group but 3.96±1.08 days in drain group there was no mortality. Conclusion: Routine chest tube drain insertion is not necessary following uncomplicated surgical ligation of PDA through transaxilary route. Chest drain was associated with postoperative complications. JAFMC Bangladesh. Vol 15, No 2 (December) 2019: 155-157